PENGAPLIKASIAN ABU PURUN TIKUS (Eleocharis dulcis) UNTUK MEMPERBAIKI pH AIR ASAM - Iswahyudi, Herry; Vina, Vina (Universitas Lambung Mangkurat, 2023)
Water is a component that is needed by all living things, both humans, animals and plants, namely as a medium for transporting food substances, a source of energy and various other needs. In this study purunrat ash was used as a neutralizer for acidic river water in Tanipah Village, Mandastana District, Barito Kuala Regency. This study aims to determine the processing of rat purun ash and determine the pH values of water before and after purun rat ash is applied. The treatment given to each water sample was 8 treatments consisting of M0 (control/without treatment), M1 (rat purun ash 0.1 g/400 ml water), M2 (rat purun ash 0.2 gr/400 ml water), M3 (rat purun ash 0.3 gr/400 ml water), M4 (mouse purun ash 0.5 gr/400 ml water), M5 (rat purun ash 1 gr/400 ml water), M6 (rat purun ash 2 gr/400 ml water), M7 (rat purun ash 3 gr/400 ml water). The results obtained were that the best treatment in neutralizing the pH of acidic water was M3 (0.3 g rat purun ash/400 ml of water) capable of raising the pH of the water to 7, as much as 1.4 with an initial pH value of 5,6.